MODEL KONSELING KELOMPOK UNTUK MENINGKATKAN SELF-EFFICACY MAHASISWA - Awaluddin Tjalla, Herdi (Perspektif Ilmu Pendidikan, 2013)
This research aimed at producing a group counselling model to improve the students’ self-efficacy at Gudance and Counselling Department of School of Education, State University of Jakarta. The students 2007 academic year were writing their thesis. Taking a place in Gudance and Counselling Department of School of Education, State University of Jakarta, the research was conducted in the academic year of 2011/2012. The sample of 48 students were selected by random sampling from the students registered ini 2007. The research and development method was employed and the data were collected using the instrument of Multicultural Counselling Competence for counsellor candidates, which had been validated and its realibility had been tested. The findings wre classified into two groups. The first indicated 52.1% of the students have high self-efficacy. The second, the predictive effective group counselling model predicted was behavior-cognitive group counselling. The prodused model consisted of rationale, objective, main componen, format, session, counsellor’s roles, counselling phases, and success indicator. The research recommended Gudance and Counselling Department, students and researchers to do further research testing the effectivness of the model to improve students’ self-efficacy.